Comparative study of 3D reconstruction of rat sciatic nerve microvessels using Evans blue and lead oxide. (November 2014) - Zhu, Zhaowei; He, Bo; Mao, Yihua; Zhao, Lina; Zhou, Xiang; Zhu, Qingtang; Zhu, Jiakai; Tang, Maolin; Liu, Xiaolin
<x content-type="archive" xml:space="preserve">Abstract</x> Background: The blood supply of peripheral nerve grafts is one of the important factors that affect nerve regeneration. Many investigators have studied how intraneural microvessels are distributed and ways to promote the angiogenesis of grafts. However, there still does not exist an ideal intraneural microvascular model. The purpose of this study was to compare the three-dimensional (3D) reconstruction of microvessels of the sciatic nerve in Sprague-Dawley (SD) rats after systemic perfusion with Evans blue (EB) or lead oxide. Methods: Ten adult SD rats were randomized to a fluorography group (EB) or radiography group (lead oxide). After administration of the perfusion agents, imaging information was obtained by fluorescence microscopy and micro-computed tomography (μCT). Three-dimensional reconstruction was performed, and the diameter of microvessels at a constant distance (a cross-section was taken every 1 mm), the vascular index, and volume were measured. Two-dimensional (2D) images were obtained by serial sectioning and μCT scanning using the two methods described. Results: In the EB group, the diameter, vascular area, and vascular index of microvessels were 11·79 ± 7·23 μm, 0.14 ± 0.05 mm2, and 24·19 ± 5·03%, respectively, and in the lead oxide group 26·45 ± 11·81 μm, 0.06 ± 0.02 mm2, and 10·73 ± 2·06%, respectively. Microvessels with diameters <20 μm were visualized better in the EB group than in the lead oxide group (P < 0·01). However, there was no significant difference between the groups in the visualization of microvessels with diameters 20–49 μm (P > 0·05). Conclusions: Both EB and lead oxide can be used for 2D study of intraneural microvessels and 3D observation after reconstruction. Lead oxide is easy to use, and though its resolution is lower than that of EB for smaller microvessels with diameters <20 μm, it is more suitable for studying a large sample volume.